2003
DOI: 10.1002/ps.655
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of the role of alternative oxidase in the performance of strobilurin and related fungicides acting at the Qo site of Complex III

Abstract: Mitochondrial respiration conserves energy by linking NADH oxidation and electron-coupled proton translocation with ATP synthesis, through a core pathway involving three large protein complexes. Strobilurin fungicides block electron flow through one of these complexes (III), and disrupt energy supply. Despite an essential need for ATP throughout fungal disease development, strobilurins are largely preventative; indeed some diseases are not controlled at all, and several pathogens have quickly developed resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
2
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 65 publications
2
118
2
6
Order By: Relevance
“…NADH is oxidized by two different dehydrogenases. An external NADH dehydrogenase (NDE) enables cytoplasmic NADH to be used directly, while an internal NADH dehydrogenase (NDI) catalyses a rotenone-insensitive oxidation of mitochondrial NADH generated by TCA cycle (Wood and Hollomon, 2003). NADH is unable to pass through the inner mitochondrial membrane so it is oxidized outside of the mitochondria by NDE and donate their electron directly to ubiquinone (UQ) pool (Siedow and Day, 2000;Møller, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NADH is oxidized by two different dehydrogenases. An external NADH dehydrogenase (NDE) enables cytoplasmic NADH to be used directly, while an internal NADH dehydrogenase (NDI) catalyses a rotenone-insensitive oxidation of mitochondrial NADH generated by TCA cycle (Wood and Hollomon, 2003). NADH is unable to pass through the inner mitochondrial membrane so it is oxidized outside of the mitochondria by NDE and donate their electron directly to ubiquinone (UQ) pool (Siedow and Day, 2000;Møller, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1A, B), so the third reason is unsuitable. Furthermore, Wood and Hollomon (2003) reported that NDE lack inhibitors, so that the second and third reasons can also be eliminated. The effect of SHAM on NADH oxidation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticeable that QoI resistant oomycete pathogens are sensitive to cyazofamid, a QiI fungicide that blocks electron flow through the second quinone binding site of cytochrome bc-1 which faces the inside of the mitochondrial matrix (Mitani et al, 2005). Cyazofamid may be used as a partner to QoIs in resistance management programmes, although it should be recognised that both QoI and QiI fungicides activate alternative oxidase, which causes low levels of resistance to both fungicide groups (Wood and Hollomon, 2003;Hollomon et al, 2005;Gisi et al, 2005). General FRAC guidelines for use of QoI fungicides include the following key instructions: -Apply QoI fungicides at effective rates and intervals, according to manufacturers' recommendations.…”
Section: Qois (Quinone Outside Inhibitors "Strobilurins")mentioning
confidence: 99%
“…The phenomenon was attributed to the additional supply of energy due to increased alternative oxidase (AOX) activity or due to other reasons (Pieczul and Perek 2015). Previous studies indicated that AOX can be induced by fungicides causing ubiquinone inhibition (QoI), what increased survival of fungi under QoI treatment (Wood and Hollomon 2003).…”
mentioning
confidence: 99%